Population Aging and Long-Term Fiscal Sustainability in Austria - Eskesen, Leif (IMF Working Papers; Working Paper ;, 2002)
Austria faces significant population aging. This will increase public spending on pensions, health care, and long-term care, while tax and social security revenues will fall. This paper analyzes the fiscal burden facing Austria due to aging and the policy steps necessary to address it. The paper finds that Austria is not well prepared to meet the fiscal burden of aging and that fiscal sustainability is threatened, even under fairly optimistic assumptions about the effects of recent pension and labor market reforms. Consequently, to ensure long-term sustainability, pension reform must go further and other saving measures might also be necessary.